User Experience as a Challenge for Cognitive Psychology and Ergonomics - Marchitto, Mauro; Cañas, José (Human Technology, 2011)
Research on human–technology interaction has been concerned with assessing the experience of interacting with technology that is already in the process of being designed. However, the challenge nowadays is to help industry find out what technology should be designed. In this new context, cognitive psychology and ergonomics should be able to assist the innovation process through an analysis of the actions that constitute human life and the role that technology plays in these actions. In this paper, we present our approach to the definition of the role of cognitive psychologists and cognitive ergonomists in the innovation process. We aim to define new concepts and methodologies that would help in the process. One example, taken from a research project from a Spanish consortium of universities and industries, is described